Ruth Finer Mintz (ed. y trad.), Modern Hebrew Poetry. A bilingual anthology. University of California Press, Berkeley y Los Angeles, 1966. LIV, 371 pp. - Molina, Sergio (Estudios de Asia y África, 1967)
-